反復コンウェイのチェーン表記

反復コンウェイのチェーン表記

\[ f\left(x\right)=X\rightarrow\left(x\right)\rightarrow q \]
とすると、

\[ X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right)=f^{p\circ}\left(X\right) \]

となる。

-

\(\rightarrow\)はコンウェイのチェーン表記

\begin{align*} X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right) & =f\left(\left[X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right)\right]_{p\rightarrow p-1}\right)\\ & =\left[f\left(X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right)\right)\right]_{p\rightarrow p-1}\\ & =\left[f^{p\circ}\left(X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right)\right)\right]_{p\rightarrow0}-\sum_{k=0}^{p-1}\left[\left[f^{\left(k+1\right)\circ}\left(X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right)\right)\right]_{p\rightarrow p-\left(k+1\right)}-\left[f^{k\circ}\left(X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right)\right)\right]_{p\rightarrow p-k}\right]\\ & =\left[f^{p\circ}\left(X\rightarrow\left(p+1\right)\rightarrow\left(q+1\right)\right)\right]_{p\rightarrow0}\\ & =f^{p\circ}\left(X\rightarrow1\rightarrow\left(q+1\right)\right)\\ & =f^{p\circ}\left(X\right) \end{align*}

ページ情報

タイトル

反復コンウェイのチェーン表記

URL

https://www.nomuramath.com/sthmu0z7/

SNSボタン